2018
DOI: 10.1002/csr.1510
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ethical climate and employees' organizational citizenship behavior on U.S. fashion retail organizations' sustainability performance

Abstract: To support businesses' efforts to improve sustainability performance, the role of employees should not be neglected, as organizational citizenship behavior (OCB) can improve the effectiveness and flexibility of a business as a whole. Given the potential impact of OCB on organizations' performance, this study investigated how the role of employees' OCB can help to achieve the triple bottom line of sustainability-financial, social and environmental performance. Using U.S. fashion retail employees as the sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 46 publications
4
39
0
2
Order By: Relevance
“…Prior studies have claimed that it is crucial for organizational members to perceive positive workplace attitudes and engage in positive workplace behaviors to achieve organizational sustainability since employee are key stakeholders to organizational success (e.g., [66]). In this perspective, organizational citizenship behavior has been argued to be able to improve an organization's overall sustainability [67]. Therefore, the study extends CSR literature as it suggests that employee volunteering can result in organizational citizenship behaviors which then can improve corporate sustainability.…”
Section: Discussionmentioning
confidence: 65%
“…Prior studies have claimed that it is crucial for organizational members to perceive positive workplace attitudes and engage in positive workplace behaviors to achieve organizational sustainability since employee are key stakeholders to organizational success (e.g., [66]). In this perspective, organizational citizenship behavior has been argued to be able to improve an organization's overall sustainability [67]. Therefore, the study extends CSR literature as it suggests that employee volunteering can result in organizational citizenship behaviors which then can improve corporate sustainability.…”
Section: Discussionmentioning
confidence: 65%
“…Employees are key to an organization for achieving environmental performance since attaining a sustainable environment is an urgent matter for organizations to achieve the economic objectives in close coordination with the natural environment [ 65 ]. The actions of individuals, especially employees in organizations, can contribute significantly to the achievement or non-achievement of a sustainable environment.…”
Section: Theoretical Framework and Related Literaturementioning
confidence: 99%
“…Traditionally, researchers, scholars, and practitioners have considered employee attitude as a critical factor in successful change efforts in organizations (Yousef, 2000;Bernerth, 2004;Bellou, 2007;Khatoon and Farooq, 2015;Zakaria and Abdullah, 2018). Lee and Ha-Brookshire (2018) found that the role of employees on the organization"s overall sustainability performance is highly important. Lacy et al (2009) argued that organizations must invest in helping employees acquire and build the knowledge, skills, and attitudes required to carry out sustainability-related initiatives.…”
Section: The Role Of Employee's Attitude Toward the Implementation Ofmentioning
confidence: 99%
“…For example, Andrew (2017) argued that individual"s attitudes, beliefs, and behaviors can affect the intended organizational change as he explained, "employees in organization may contribute toward the achievement of the organization"s objective and its efforts for development at varying scale depending on how he/she perceive" (p. 2). The role of employees should not be neglected in supporting businesses" efforts to improve sustainability performance (Lee and Ha-Brookshire, 2018).…”
Section: The Role Of Employee's Attitude Toward the Implementation Ofmentioning
confidence: 99%
See 1 more Smart Citation